1998
DOI: 10.1080/001401398186342
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of musculoskeletal alterations in worker populations not exposed to repetitive tasks of the upper limbs

Abstract: A total of 749 workers (males: 139 aged between 15 and 35 years, and 171 aged > 35 years; females: 176 aged between 15 and 35 years, and 263 aged > 35 years) performing tasks not at risk for work-related musculoskeletal disorders of the upper limbs (WMSDs) underwent a clinical examination using a standardized method. The 'anamnestic cases' were defined on the basis of pain or paraesthesia present for at least 1 week during the previous 12 months, or appearing at least once a month, and not subsequent to acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 3 publications
0
15
0
1
Order By: Relevance
“…Morse et al [ 28 ] defined UEDs as 'pain or discomfort of the hand, arm, shoulder, or neck for one continuous week or 20 days total over the previous 12 months (= chronic pain)'. The other three studies [ 16 , 29 , 30 ] also reported a specified definition of UEDs. The terms they used refer to musculoskeletal disorders located in the upper extremity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morse et al [ 28 ] defined UEDs as 'pain or discomfort of the hand, arm, shoulder, or neck for one continuous week or 20 days total over the previous 12 months (= chronic pain)'. The other three studies [ 16 , 29 , 30 ] also reported a specified definition of UEDs. The terms they used refer to musculoskeletal disorders located in the upper extremity.…”
Section: Resultsmentioning
confidence: 99%
“…In the case definitions they specified the duration of the complaints within the last 12 months and the sensation the patients must have beside pain such as discomfort or paraesthesia. In addition, Batavi et al [ 30 ] and Bernard et al [ 29 ] excluded UEDs caused by an acute trauma. Bernard et al [ 29 ] made the case definition even more specific by labeling work-relatedness of the disorder caused by the current job and the seriousness of the disorder.…”
Section: Resultsmentioning
confidence: 99%
“…Appropriate training to ManTRA users as well as employees' and management' contribution to task analysis and risk assessment process can help to gain the precise risk assessment results (4,9). ManTRA suggests that the tasks with cumulative risk scores excessive TLVs should be considered to suffer further measurements or actions to reduce obtained cumulative risk scores to TLVs to prevent WMSDs occurrences (9,12). Preventive measures should be exerted on the manual tasks that have cumulative risk scores excessive TLVs for minimizing WMSDs occurrences of anybody regions (13).…”
Section: Discussionmentioning
confidence: 99%
“…Work-related musculoskeletal disorders (WRMSDs) are common worldwide, and more common among women [see, e.g., Ashbury, 1995;Guo et al, 1995;De Zwart et al, 1997;Battevi et al, 1998;Zetterberg and Ö fverholm, 1999;Swedish Work Environment Authority and Statistics Sweden, 2003]. A plausible explanation to gender differences in WRMSDs might be exposure differences or differences in exposure levels between male and female workers.…”
Section: Introductionmentioning
confidence: 99%